Does Impulsive Buying Lead to Compulsive Buying in Metaverse? A Dual-Stage Predictive-Analytics SEM-ANN Analysis. The Empirical Study from Vietnam - Thao Cong Phan, Tien; Thanh Nguyen, Luan; Quan Dang, Tri (Thailand and The World Economy, 2025)
The expansion of the metaverse, an all-encompassing digital environment that integrates virtual reality, augmented reality, and the internet, has fundamentally altered human interaction and behavior, including online purchasing. Due to its interactivity and immersion, the metaverse provides a unique experience that blurs the line between the physical and digital realms. A multitude of prominent corporations have established virtual retail locations within the metaverse, enabling customers to virtually examine merchandise by utilizing photorealistic avatars; this has led to a surge in revenue. Considerable scholarly investigation has been devoted to the subject of impulsive online shopping behavior. Furthermore, the evolution of the metaverse may intensify predispositions towards impulsive and compulsive buying. Nevertheless, there is a dearth of empirical research examining the impact of the metaverse on consumer decision-making. The primary objective of this research endeavor is to examine the impact of the metaverse on compulsive and impulsive buying behavior. Specifically, this study will investigate the influence of perceived value, social influence conformity, metaverse engagement presence, and virtual identity alignment. The utilization of the S-O-R framework in this study provides valuable insights into consumer behavior in virtual environments, which have substantial ramifications for developers and businesses operating in the metaverse. In order to enhance comprehension of consumer behavior in the metaverse, this research utilized a non-probability judgmental sampling technique to select 186 respondents who are active participants in online purchasing within the metaverse in Vietnam. Next, the PLS-SEM and ANN analyses were applied to test the relationship among variables. The research substantiates the importance of impulsive buying and its impact on compulsive buying within the metaverse setting by identifying two influential factors (PCV and MEP) that determine impulsive buying. This study offers significant contributions to the understanding and administration of consumer behavior in the metaverse.